Psychological inflexibility and valuing happiness: Dangerous liaisons - Valdivia-Salas, Sonsoles; Lombas, A. Sebastian; Salvador, Sonia; López-Crespo, Ginesa (Frontiers in Psychology, 2022)
Previous evidence has shown that excessive valuing happiness may relate to lower psychological well-being across cultures. Considering the lack of data with Spanish population, we examined the relation between tightly holding happiness emotion goals and subjective well-being in a sample of Spanish women, and explored the mediation role exerted by psychological inflexibility components (namely, cognitive fusion and experiential avoidance) in the relation between valuing happiness and subjective well-being. A female adult sample (n = 168) filled out measures of excessive valuing happiness, psychological inflexibility, positive affect, negative affect and life satisfaction. Valuing happiness only showed positive total effects on negative affect and strong direct effects on both cognitive fusion and experiential avoidance. Analyses revealed the mediating roles exerted by psychological inflexibility components, with experiential avoidance leading to lower pleasure; and cognitive fusion leading to greater displeasure and lower life satisfaction. Psychological inflexibility components explained between 40% and 80% of the total effect of valuing happiness on our outcome variables. Our findings highlight the need for further research on the benefits of hedonic versus values-based approaches to happiness.